AN ANALYSIS OF TECHNIQUES OF ADJUSTMENT IN TRANSLATING RELIGIOUS TEXT VOCABULARIES (A STUDY ON SERIES OF A HANDBOOK ON THE REVELATION TO JOHN) - Sujatmiko Sujatmiko (Journal of English Language Teaching and English Linguistics, 2015)
research is entitled â€œAn Analysis of Techniques of Adjustment in Translating ReligiousText Vocabularies (A Study on Series of A Handbook on the Revelation to John)â€. It is about howreligious text vocabularies are translated by using technique of adjustment. It is aimed to find types oftechniques of adjustment and their subtypes.This research uses qualitative method to analyze the data. Techniques of analyzing data in thisresearch consist of 3 components; they are (1) reducing the data, (2) explaining the data, and (3)taking a conclusion. Reducing data is a process of selecting, focusing, simplifying and abstracting thedata. Explaining the data is a process of organizing information and arranging the completenarration. Taking a conclusion is a process of drawing conclusion from the data. The data sources ofthis research are A Handbook on the Revelation to John and its Indonesian translation entitled SeriPedoman Penafsiran Alkitab Wahyu Kepada Yohanes.After conducting the research, the researcher finds 73 data. Alteration technique is in the firstposition with 55 data or 74.2%. Then, addition technique is in the second position with 12 data or16.4%. The last is subtraction technique with 6 data or 8.2%. Addition technique is divided into 3classifications, i.e. obligatory specifications (3 data or 4.1%), amplifications (7 data or 9.6%), andclassifiers (2 data or 2.7%). Subtraction technique is divided into 2 classifications, i.e. conjunctions(3 data or 4.1%) and formulae (3 data or 4.1%). Alteration technique is divided into 7 classifications,i.e. sounds (15 data or 20.5%), categories (6 data or 8.2%), word classes (2 data or 2.7%), order (6data or 8.2%), clause and sentence structure (1 datum or 1.4%), semantic problems involving singleword (19 data or 26%), and semantic problems involving exocentric expression (6 data or 8.2%).This research is expected to open wide opportunities and challenges to academicians,646333255especially those in translation linguistics sphere to deepen their research and study,especially in translating the holy religious texts in order to be a new contribution to the translationfields.